A mosquito is born - White, William, 1934-; White, Sara Jane (New York : Sterling Pub. Co., 1978)
Describes and illustrates in detail the habitat, physical characteristics, and life cycle of mosquitoes and how they transmit diseases.
Includes index.
Keywords: Mosquitoes -- Juvenile literature; Mosquitos -- Literatura juvenil; Mosquitoes